2018
DOI: 10.1016/j.kjms.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4.8 Fr and 6 Fr ureteral stents on stent related symptoms following ureterorenoscopy: A prospective randomized controlled trial

Abstract: The effects of ureteral stent diameters on ureteral stent‐related symptoms were evaluated by using Turkish‐validated Ureteral Stent Related Symptoms Questionnaire (USSQ). Datas on 126 patients underwent uncomplicated flexible ureterorenoscopy and 62 patients underwent uncomplicated semirigid ureteroscopy surgery without stent insertion (group 3) were collected. Patients were randomized preoperatively in a double‐blind fashion to 4.8 French (group 1) and 6 French (group 2) ureteral JJ stents groups. The first f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
(32 reference statements)
2
22
0
3
Order By: Relevance
“…However, these studies did not pay attention to the different features of the DJ stents. According to a study grouped according to stent properties by Alkan Çubuk et al after URS operations, Ureteral Stent Related Symptoms Questionnaire (USSQ) scores were significantly low both in the 1st week po and after stent removal for the group without stent compared to the group with stent inserted (17). In our study, in general all groups had significant falls in NPS on the po 3rd and 7th days compared to preop values, and this fall was more pronounced in the NPS examined after stent removal (Tables 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not pay attention to the different features of the DJ stents. According to a study grouped according to stent properties by Alkan Çubuk et al after URS operations, Ureteral Stent Related Symptoms Questionnaire (USSQ) scores were significantly low both in the 1st week po and after stent removal for the group without stent compared to the group with stent inserted (17). In our study, in general all groups had significant falls in NPS on the po 3rd and 7th days compared to preop values, and this fall was more pronounced in the NPS examined after stent removal (Tables 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…We did not take into consideration other stent characteristics including length, coil length or material, previously proven to influence stent symptoms and failure [4,18,19]. In addition, although pain and lower urinary tract symptoms (LUTS) have been included in the definition of ureteral stent failure in some reports of adult ureteral stenting, and though some studies on adult population found that smaller diameter DJS improved the severity of these symptoms, these symptoms are usually quantified by 'quality of life' questioners and personal interviews, making it difficult to assess in pediatric patients [10,11]. Thus, these complications were excluded from our study [5].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lee et al, in their study of stent failure in the pediatric population, have concluded that 3Fr DJS was the only risk factor for stent failure [5]. On the other hand, some studies have found that the use of smaller diameter DJS lowers the severity of DJS-related symptoms [10,11]. In addition, some pediatric urologists tempt to avoid passing a DJS through pediatric uretero-vesicular junction (UVJ), to avoid UVJ injury and subsequent stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Common type of stents include metallic stents 5,16,17 and polymeric stents. [27][28][29][30][31][32][33][34][35][36]…”
Section: Innovation Driven By Patients' Health-related Quality Of Lifmentioning
confidence: 99%
“…These studies showed no differences between stone-free rates following planned and repeated unilateral ureteroscopy (URS). 35 Based on previously discussed modifications, a dual-lumen stent with two drainage pathways was tested by Hafron et al and reported improved urine drainage when compared to single lumen stents in an ex vivo kidney model. 36…”
Section: Stent Size and Length With Their Clinical Usementioning
confidence: 99%